Impact of a Thin Sacrificial Mo Layer on the Formation of the Wide Band Gap ACIGSe Absorber/ITO Thin-Film Solar Cell Interface - Demling, Angelika; Gutzler, Rico; Almeida Alves, Cristiana Filipa; Wilks, Regan G.; Félix, Roberto; Hariskos, Dimitrios; Paetel, Stefan; Cerqueira, Rafael; Sadewasser, Sascha; Witte, Wolfram; Bär, Marcus (ACS Applied Materials and Interfaces, 2025)
The effect of a thin sacrificial Mo interlayer on the device performance of a thin-film solar cell based on a wide band gap (1.46 eV) (Ag, Cu)(In, Ga)Se2 (ACIGSe)/indium tin oxide (ITO) layer stack and its influence on the chemical composition at the absorber/transparent back contact (TBC) interface are investigated. The solar cell without a Mo interlayer exhibits an efficiency of less than 1%, whereas the inclusion of an approximately 10 nm thick Mo interlayer produces a cell with an efficiency of 10.1%, with the fill factor being more than tripled. Scanning transmission electron microscopy and energy-dispersive X-ray spectroscopy line scans show strong GaOx formation at the absorber/transparent conductive oxide (TCO) interface in a Mo-free sample and a significant decrease in the amount of GaOx in a sample with the Mo interlayer included. Cleaving the absorber/TBC interface allowed us to study the absorber back side and the exposed ITO TCO using hard X-ray photoelectron spectroscopy. The nearly complete conversion of the metallic Mo interlayer into MoSe2 and MoOx is revealed. It is suggested that the formation of MoOx, which may act as a hole-selective contact, together with inhibited GaOx formation might be responsible for the pronounced performance enhancement for the cell with the thin Mo interlayer.
CRIS-Team Scopus Importer:2025-05-30
Keywords: CIGS; GaO; HAXPES; interface; STEM; thin-film solar cell; transparent back contact; wide band gap